2014
DOI: 10.1590/s1679-45082014ao2706
|View full text |Cite
|
Sign up to set email alerts
|

Use of rituximab as a treatment for systemic lupus erythematosus: retrospective review

Abstract: Objective:To report the experience in three Brazilian institutions with the use of rituximab in patients with different clinical forms of lupus erythematosus systemic in activity.Methods:The study consisted of a sample of 17 patients with LES, who were already being treated, but that at some stage of the disease showed refractory symptoms. The patients were subdivided into groups according to the clinical manifestation, and the responses for the use of rituximab were rated as complete, partial or no response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
2
2
0
4
Order By: Relevance
“…La mortalidad y la morbilidad se relacionan con daño severo en los órganos, infecciones a causa de la inmunosupresión y eventos cardiovasculares secundarios [2]. Un estudio por parte del Centro para el Control de Enfermedades (CDC, por sus siglas en inglés) describió un aumento importante en el número anual de muertes, que pasó de 39 a 52 por cada 10 millones de habitantes y totalizó 22 861 muertes en el período entre 1979 y 1998.…”
Section: Sintomatologíaunclassified
See 3 more Smart Citations
“…La mortalidad y la morbilidad se relacionan con daño severo en los órganos, infecciones a causa de la inmunosupresión y eventos cardiovasculares secundarios [2]. Un estudio por parte del Centro para el Control de Enfermedades (CDC, por sus siglas en inglés) describió un aumento importante en el número anual de muertes, que pasó de 39 a 52 por cada 10 millones de habitantes y totalizó 22 861 muertes en el período entre 1979 y 1998.…”
Section: Sintomatologíaunclassified
“…A pesar de que se conoce esta actividad de las citoquinas, aún no se sabe completamente cómo es la participación de las células B en la fisiopatología de esta enfermedad [2].…”
Section: Fisiopatologíaunclassified
See 2 more Smart Citations
“…In addition to NETs, which are proposed as important autoantigens for the development of ANAs, patients with SLE have hyperactivity characteristics of B lymphocytes, including the typical increase in circulating plasmocytes. Experimentally, it was observed that if these cells were removed from mouse "lupus models" by genetic manipulation or antibody therapy, the chain of immune reactions would be largely suppressed, including T-cells induced abnormalities 2,3 .…”
Section: Chart 1: Characterization Of the Main Analyzed Studies Continuationmentioning
confidence: 99%